Core-periphery communication and the success of free/libre open source software projects - Kevin Crowston; Ivan Shamshurin (Journal of Internet Services and Applications, 2017)
Abstract We examine the relationship between communications by core and peripheral members and Free/Libre Open Source Software project success. The study uses data from 74 projects in the Apache Software Foundation Incubator. We conceptualize project success in terms of success building a community, as assessed by graduation from the Incubator. We compare successful and unsuccessful projects on volume of communication and on use of inclusive pronouns as an indication of efforts to create intimacy among team members. An innovation of the paper is that use of inclusive pronouns is measured using natural language processing techniques. We also compare the volume and content of communication produced by core (committer) and peripheral members and by those peripheral members who are later elected to be core members. We find that volume of communication is related to project success but use of inclusive pronouns does not distinguish successful projects. Core members exhibit more contribution and use of inclusive pronouns than peripheral members.